Berkarir di Perpajakan Berdasarkan Persepsi dan Motivasi Mahasiswa FE Unai Tentang Pajak - Seroy, Rhiezky Samuel; Susanti, Mila; Sudjiman, Lorina Siregar (Jurnal Ekonomis, 2024)
Education is one of the programs to advance and educate the nation. Education begins with the family, which generally builds a person's character and career interests. Currently, there are still great opportunities in a tax career. However, it can be seen that a person's perception and motivation in a tax career are still far in demand. The purpose of this research is to research career interests in the field of taxation based on students' perceptions and motivations about taxes. The research was conducted on FE Unai students as a population and a sample of 75 people was obtained using snowball sampling. The research uses a quantitative method with primary data through questionnaires. Measurement scale using Likert scale. Statistical analysis describes data and trends as well as significance tests, equipped with validity and reliability tests. The research provides results that career interest in taxation is significantly influenced by perceptions and motivations about taxes, both partially and simultaneously.